Lower Limb Skin Graft Failure: Incidence and Risk Factors: A Longitudinal Study - Syed Aaqil Shah, Rabia Anwar, Mahak Ali, Saba Kiran, Aiman Naseem, Hassan Kashif (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the incidence and risk factors of lower limb skin graft failure. Study design: A longitudinal study Place and duration: This study was conducted at Patel Hospital Karachi Pakistan from January 2021 to January 2022 Methodology: The study incorporated all the patients who required skin Grafts for lower limbs. Patient characteristics and diseases were noted. All Grafts were conducted with tried-and-true methods. Transplant history with immunosuppression, Anticoagulation/ antiplatelet treatments, and anatomical wound location was noted. Weight-bearing status of the wound size at the time of STSG placement, wound size 14 days post-STSG, and wound size 45 days post-STSG were examined. Patients were observed for six weeks after the transplant for graft take. Data were evaluated using SPSS version 21. Results: A total of 62 patients received 79 skin Grafts, including multiple grafts for 17 individuals. The mean age of patients was 68 ± 9.2 years. The medium BMI of patients was 28. 19 (30.6%). A total of 11 (17.74%) patients had ischemic heart disease, and 19 (30.6%) had venous insufficiency. Immunosuppressant use 4 (6.4%), Diabetes 9 (14.5 %), and Peripheral vascular disease (PVD) were observed in 24 (39%) of patients. A significant association was observed with BMI, Immunosuppressant use, and peripheral vascular disease (PVD). Conclusion: Skin Grafts on the lower limb fail more frequently than skin grafts on other body parts. Proper observation and treatment may reduce the risk of infection and hematoma. Skin graft failure rates are still high, and several contributing factors are associated with this condition. Immunosuppression use and BMI were the contributing factors in the present study Keywords: Body mass index, Immunosuppression, Lower extremity, Reconstruction, Skin grafts